Work-in-Progress: A Smart Scheduling System for Shared Interactive Remote Laboratories - Mohammed Moussa; Abdelhalim Benachenhou; Abderrahmane Adda Benatia (My University, 2017)
Online laboratories are an innovative solution for providing hands-on experience in the STEM Education. A large number of students are using remote laboratories (RL) to meet their practical needs and enriching their learning. The deployment of a unique instance of the RL cannot provide all requirements for the growing number of students. For that purpose, the use of multiple instances of RLs can produce many advantages. We propose in this paper a new method for managing access to these RLs. The implemented system provides a central point of control all requests to access to the RLs. This approach is transparent to the user. The system under development supplies an abstraction layer. The goal of the work is to build a web service through which the access to RLs is granted. The student will don’t need to reserve a time slot to access the RL. In addition, the system supports the registration of new RLs in a transparent way for teachers.
Keywords: Remote laboratories; Web services - REST; Web services; REST; Smart scheduling